2015
DOI: 10.7861/clinmedicine.15-3-239
|View full text |Cite
|
Sign up to set email alerts
|

Serum potassium levels as an outcome determinant in acute medical admissions

Abstract: The relationship between serum potassium levels and mortality in acute medical admissions is uncertain. In particular, the relevance of minor abnormalities in potassium level or variations within the normal range remains to be determined. We performed a retrospective cohort study of all emergency medical admissions to St James's Hospital (Dublin, Ireland) between 2002 and 2012. We used a stepwise logistic regression model to predict in-hospital mortality, adjusting risk estimates for major predictor variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
7
39
0
4
Order By: Relevance
“…Hypernatraemia in present study was noted in 4% of the critically ill children. This finding is in consistent with the studies by Michael D. Waite et al, [14] Richard Conway et al [21] and Singhi et al [24] who observed hypokalaemia in 4.9% and 5.4% respectively, which were nearly comparable with our results.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Hypernatraemia in present study was noted in 4% of the critically ill children. This finding is in consistent with the studies by Michael D. Waite et al, [14] Richard Conway et al [21] and Singhi et al [24] who observed hypokalaemia in 4.9% and 5.4% respectively, which were nearly comparable with our results.…”
Section: Discussionsupporting
confidence: 94%
“…In hypokalaemic group, mortality was estimated to be 1.2 times higher than normokalaemia consistent with results by Richard Conway et al, [21] Singhi et al [23] and Subba Rao et al [7] noted 27.7% mortality in hypokalaemic children.…”
Section: Mortalitysupporting
confidence: 87%
See 1 more Smart Citation
“…Hyperkalemia, usually defined as blood potassium level >5.0 mmol/L, is a concern in patients with HF in everyday clinical practice and can be a life‐threatening condition . Hyperkalemia with high potassium levels (eg, >6.0 mmol/L) may lead to cardiac arrhythmias and death, but even potassium levels of >5.0 mmol/L have been associated with increased mortality in patients with acute‐care hospital admission and in patients with HF …”
mentioning
confidence: 99%
“…A range for [K + ] in the cerebral spinal fluid for non-diseased state humans in one study was found to be 2.4-3.0 mmol/L and 3.5-4.70 mmol/L in plasma (Pye & Aber, 1982). A twofold increase in plasma [K + ] to 7 or 8 mmol/L in humans will likely lead to death, unless rapidly reduced (Conway, Creagh, Byrne, O'Riordan, & Silke, 2015;Gennari, 1998;Nyirenda, Tang, Padfield, & Seckl, 2009). A recent study measured the [K + ] in abscesses in the human brain and found the levels to have an average 10.6 ± 4.8 mmol/L (Dahlberg, Ivanovic, Mariussen, & Hassel, 2015).…”
Section: Discussionmentioning
confidence: 99%